Fatigue of structural adhesives under stress concentrations: Notch effect on fatigue strength, crack initiation and damage evolution. (November 2020) - Beber, V.C.; Schneider, B.
Graphical abstract: Highlights: Majority of fatigue lifetime (60–95%) is spent on crack initiation and shortened by an increasing stress concentration factor. Crack initiation causes sudden damage increase. Correlation between the slope of the SN curve and the inverse of the highly stressed region. Model proposing a relationship between notched fatigue strength, highly stressed region and stress concentration factor. Abstract: The effect of stress concentrations on the fatigue behaviour of two structural adhesives, relevant materials in lightweight applications, was investigated regarding fatigue strength, crack initiation lifetime, damage evolution and fracture behaviour. Internally and externally notched adhesive bulk specimens were tested under constant amplitude loading with a stress ratio of 0.1. Majority of fatigue lifetime (60–95%) was spent on crack initiation, which was shortened by an increasing stress concentration factor. Crack initiation causes a sudden damage increase near to failure. A model was proposed correlating the fatigue strength of notched specimens with highly stressed region and stress concentration factor.